Novel approaches for the diagnosis of drug-resistance, treatment response, and infectiousness in patients with tuberculosis (the eDIToR study – Diagnosis Infectiousness and Treatment Response) - Venter, Rouxjeane (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.